2016
DOI: 10.3389/fpsyg.2016.01398
|View full text |Cite
|
Sign up to set email alerts
|

“Female Preponderance” of Depression in Non-clinical Populations: A Meta-Analytic Study

Abstract: Clinical observations and research suggest a female preponderance in major depressive disorder. However, it is unclear whether a similar gender difference is found for the reporting of depressive symptoms in non-clinical populations. The present meta-analysis was conducted to address this issue. We searched for published papers targeting non-clinical populations in which the 21-item Beck Depression Inventory (BDI) was used. Eighty-four papers (91 studies) published between 1977 and 2014 were included in the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 74 publications
(85 reference statements)
2
29
1
4
Order By: Relevance
“…The DNA methylation levels were found to be very low (1% to 3%) for these selective sites ( Figure 1C). Moreover, it has been argued that women have stronger tendency towards depression than men [25], but in our analysis no difference was observed among male and female subgroups, indicating that gender has no impact on DNA methylation levels for these particular genes in depression phenotype. In conclusion, DLG4 and GJA-1 did…”
contrasting
confidence: 37%
“…The DNA methylation levels were found to be very low (1% to 3%) for these selective sites ( Figure 1C). Moreover, it has been argued that women have stronger tendency towards depression than men [25], but in our analysis no difference was observed among male and female subgroups, indicating that gender has no impact on DNA methylation levels for these particular genes in depression phenotype. In conclusion, DLG4 and GJA-1 did…”
contrasting
confidence: 37%
“…The purpose of this step was to simultaneously examine the fixed and random effects, corresponding to the three types of neighborhoods. Thus, as shown As widely reported in the literature, women are at greater risk for depression, and have more negative perceptions of residential neighborhoods, than men [5,[15][16][17][18][19][20]52]. We therefore performed a gender-stratified analysis (models M1W and M2W for women, and M1M and M2M for men).…”
Section: Discussionmentioning
confidence: 95%
“…The proportion of individuals with depression varied between a minimum of 0.9% and a maximum of 33.1% for the 50 residential neighborhoods in the SIRS survey ( Figure 2). Depression was reported more frequently in the most deprived neighborhoods (those with a yearly household income <€6004 by consumption unit on average), which are located in the northern part of the study As widely reported in the literature, women are at greater risk for depression, and have more negative perceptions of residential neighborhoods, than men [5,[15][16][17][18][19][20]52]. We therefore performed a gender-stratified analysis (models M1W and M2W for women, and M1M and M2M for men).…”
Section: Spatial Distribution Of Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al 31 carried out a meta-analytic study to examine the female preponderance in depressive disorders and discovered that women in the nonclinical population reported higher levels of depressive symptoms than men. Other studies have previously reported that unemployed adults were at an elevated risk of developing major depression.…”
Section: Discussionmentioning
confidence: 99%